# Recurrence relation with Square roots in each term..

Hi experts,
How to solve a recurrence relation that have Square roots in each term...

I can solve the normal recurrence relation problem (that hav no square roots)

Give me some idea...

Q will be like this

ROOT(Rn) = ROOT(Rn-1)+ 2.ROOT(Rn-2)  with initial condition R0=R1=1

Rosh :)
LVL 23
###### Who is Participating?

x

Commented:
for r0=r1=1
Rn = (((-1)^n+2*2^n)/3)^2
is correct
((-1)^0 + 2*2^0)/3 = 1
((-1)^1 + 2*2^1)/3 = 1
0

Commented:
Rn = Sn²
where
Sn = (Sn-1) + 2×(Sn-2)
0

Author Commented:
Thankx for ur comment :)

Calculated associated equation
square(X) = X + 2
and itz roots are (x-2)(x+1)

C1 = u(-1)+v(2)
C2 = u.square(-1)+ v. square(2)

And reached the result

Cn = (-1/3)(-1)^n + (1/3)(2)^n

this is the Recurrence relation for "Sn = (Sn-1) + 2×(Sn-2)"

Is this correct?

Rosh :)
0

Commented:
or in closed form
Rn = (((-1)^n+2^(n+1))/3)^2
0

Commented:
Sorry, didn't see you had solved it
0

Author Commented:
Can u show me some steps...
0

Author Commented:
Hi, you can see the question here http://www.coolgoose.com/sites/puttalu/
0

Commented:
They were different because you used C1=C2=1, while I used R0=R1=1
0

Author Commented:
So, for this Q http://www.coolgoose.com/sites/puttalu/ which is correct ?
Rosh :)
0
Question has a verified solution.

Are you are experiencing a similar issue? Get a personalized answer when you ask a related question.

Have a better answer? Share it in a comment.